ANALISIS KEMAMPUAN PSIKOMOTORIK SISWA TERHADAP MATERI PRODUKTIF DI SMKN 2 BANDA ACEH - Rahmi Isna; sadrina; Malahayati (LPPM, Universitas Negeri Jakarta, 2023)
Capacity can be developed into amazing skills that can boost personal creativity. A person's abilities, skills, or psychomotor abilities are all related. This study aimed to assess the psychomotor proficiency of SMKN 2 Banda Aceh students. P1, P2, and P3 of the psychomotor scale were used in this study to examine imitation, manipulation, and articulation. Interviews were done as part of the qualitative research process. Both in-person and online interviews using the WhatsApp app were done by visiting the informant at school. In the odd semester of 2020–2021, the interviews' findings indicate that students' psychomotor skills in productive material are restricted to P1 or imitation. Each student receives homework assignments from the teacher as part of the learning process. This is due to the COVID-19 epidemic, which outlawed busy activities in classrooms and forced learning to continue online. Lack of action in the lab causes unskilled students, therefore the teacher employs real-world video tutorial media that the students can copy. Teachers find evaluating students' psychomotor skills challenging because they have limited resources and can only evaluate their knowledge abilities.